Does circadian rhythm influence gastrointestinal toxicity?. Issue 2 (June 2020) - Hofmeister, Elisa N.; Fisher, Sophie; Palesh, Oxana; Innominato, Pasquale F.
Abstract : Purpose of review: The current review outlines the existing research on the impact of circadian rhythm on gastrointestinal toxicity associated with cancer treatment and explores clinical evidence for utilizing circadian-based approaches in addressing gastrointestinal symptoms such as nausea, vomiting, diarrhea, mucositis, and hepatotoxicity. Recent findings: Recent evidence highlights circadian control of gastrointestinal physiology of appetite, digestion, nutrient absorption, and cellular proliferation in the digestive system. In addition, animal models support the mechanistic rationale of using chronotherapy (a type of anticancer therapy delivered at specific times with the goal of producing less toxicity and greater treatment response) to minimize gastrointestinal-impact of systemic cancer treatments. In addition, earlier research demonstrates that many chemotherapeutic agents are responsive to circadian timing in animals. On the contrary, clinical trials focused on minimizing gastrointestinal toxicity using chronotherapy have been limited in recent years and have not yielded the efficacy initially hoped for. Instead, researchers focused on understanding circadian rhythm's influence on the gastrointestinal system at a mechanistic level as well as measuring circadian rhythm at an individual level. Summary: Although using circadian timing is a promising target for reducing gastrointestinal toxicity, recent evidence suggests that more research is needed to understand circadian rhythm before circadian-based interventions can be developed that will result in lessening of gastrointestinal toxicity.